Design, microwave synthesis, and molecular docking studies of catalpol crotonates as potential neuroprotective agent of diabetic encephalopathy - Shuanglin Liu (Nature Portfolio, 2020)
Abstract Catalpol has gained increasing attention for its potential contributions in controlling glycolipid metabolism and diabetic complications, which makes used as a very promising scaffold for seeking new anti-diabetic drug candidates. Acylation derivatives of catalpol crotonate (CCs) were designed as drug ligands of glutathione peroxidase (GSH-Px) based on molecular docking (MD) using Surfex-Docking method. Catalpol hexacrotonate (CC-6) was synthesized using microwave assisted method and characterized by FT-IR, NMR, HPLC and HRMS. The MD results indicate that with the increasing of esterification degree of hydroxyl, the C log P of CCs increased significantly, and the calculated total scores (Total_score) of CCs are all higher than that of catalpol. It shows that CCs maybe served as potential lead compounds for neuroprotective agents. It was found that the maximum Total_score of isomers in one group CCs is often not that the molecule with minimum energy. MD calculations show that there are five hydrogen bonds formed between CC-6 and the surrounding amino acid residues. Molecular dynamics simulation results show that the binding of CC-6 with GSH-Px is stable. CC-6 was screened for SH-SY5Y cells viability by MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) assay, the result indicates CC-6 can effectively reverse SZT induced cells apoptosis with dose-dependent manner, which can indirectly show that CC-6 is a potential neuroprotective agent.